Preparation and application of aerogel thermal insulation film

By adopting a three-layer sandwich structure aerogel insulation film, using materials such as silicone matrix, titanium dioxide ultrafine powder, flame retardant and polyester silica composite, the problem of insufficient thermal insulation performance of existing porous materials is solved, and high-efficiency heat insulation and mechanical strength are improved, and good moisture resistance and flame retardant properties are achieved.

CN118560126BActive Publication Date: 2025-04-01SUZHOU KANGLIDA PRECISION ELECTRONICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410648532.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-23
Publication Date
2025-04-01
Estimated Expiration
2044-05-23

AI Technical Summary

Technical Problem

The thermal insulation performance of existing porous materials is difficult to meet the current demand for high-power electronic products, especially in terms of temperature interference to product components and user safety.

Method used

Aerogel thermal insulation film with a three-layer sandwich structure includes a silicone cured protective layer and aerogel thermal insulation layer. The aerogel thermal insulation layer consists of a silicone matrix, titanium dioxide ultrafine powder, flame retardant and polyester silica composite. The thermal insulation performance is improved through polyester nano-limiting and hydrophobic modification technology.

Benefits of technology

It significantly improves the thermal insulation performance and mechanical strength of the thermal insulation film, has good moisture resistance and flame retardant properties, avoids powder loss, does not require additional thermal protection film, and is green and environmentally friendly in the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118560126B_ABST
    Figure CN118560126B_ABST
Patent Text Reader

Abstract

The present application relates to a novel aerogel thermal insulation film and a preparation method thereof, which comprises a first layer, a second layer and a third layer, wherein the first layer and the third layer are both siloxane cured protective layers, and the second layer comprises an aerogel thermal insulation layer; the ultra-thin polydimethylsiloxane cured layer is Dow Corning No. 184 silica gel; the aerogel thermal insulation layer comprises a silica gel matrix, ultrafine titanium dioxide powder, a flame retardant, and a polyester silica composite; the silica gel matrix comprises 9110T silica gel or Dow Corning No. 184 silica gel. The present application has the effect of improving the thermal insulation performance, flame retardancy and moisture resistance of the aerogel thermal insulation film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of thermal insulation films, and in particular to the preparation and application of an aerogel thermal insulation film. Background Art

[0002] With the advent of the 5G era, the power consumption of consumer electronic products is increasing, and the corresponding heat is also increasing. From the perspective of the stability, safety and service life of electronic products, high-power electronic products need to be treated with corresponding heat conduction and heat dissipation. In order to avoid the temperature from interfering with some important components of the product or causing harm to the user, directional heat conduction and heat dissipation design is usually used in thermal design, in which thermal insulation materials play an important role.

[0003] Porous material is one of the commonly used thermal insulation materials, such as aerogel insulation film; however, porous materials have many gaps inside, which contain inert gas or air, making the thermal conductivity very low. But with the development of the times, the thermal insulation performance of existing porous materials can no longer meet current needs, so it needs to be improved. Summary of the invention

[0004] In order to improve the thermal insulation performance of porous thermal insulation materials, the present application provides an aerogel thermal insulation film and a preparation method thereof.

[0005] The present application provides an aerogel thermal insulation film and a preparation method thereof using the following technical solutions:

[0006] In the first aspect, the present application provides an aerogel thermal insulation film, which adopts the following technical solution:

[0007] An aerogel thermal insulation film comprises a first layer, a second layer and a third layer, wherein the first layer and the third layer are both siloxane cured protective layers, and the second layer comprises an aerogel thermal insulation layer;

[0008] The ultra-thin polydimethylsiloxane cured layer is Dow Corning No. 184 silicone;

[0009] The aerogel heat insulation layer comprises a silica gel matrix, ultrafine titanium dioxide powder, a flame retardant, and a polyester silica compound; the silica gel matrix comprises 9110T silica gel or Dow Corning No. 184 silica gel.

[0010] By adopting the above technical scheme, the aerogel thermal insulation film of the present application has a three-layer sandwich structure, and the first layer and the third layer are both siloxane cured protective layers, which can be directly cured on the second layer without the need for an adhesive, and can play a protective role, giving the product anti-corrosion, moisture-resistant, flexible and wear-resistant properties; the second layer is an effective ingredient mixed layer, the main components of which are polyester silica composite, transparent organic silica gel, titanium dioxide, flame retardant, etc., which can play a heat-insulating and flame-retardant function.

[0011] Preferably, the polyester-silica composite is prepared by the following method:

[0012] The polyester is mixed with hexafluoroisopropanol, stirred and spun to obtain polyester fibers; after mixing tetraethyl orthosilicate, ethanol and deionized water, the pH value is adjusted to 2-3, reinforcing materials are added, and stirred to obtain a silanol mixed solution; the polyester fiber is immersed in the silanol mixed solution, the pH value is adjusted to weak acidity to obtain a polyester silica preform, the polyester silica preform is immersed in a hydrophobic modification solution for hydrophobic modification, and then transferred to a n-hexane solution, and dried to obtain a polyester silica composite.

[0013] By adopting the above technical scheme, the polyester nano-confinement has a three-dimensional porous structure, which can improve the mechanical strength of the overall prepared polyester silica composite, and can effectively improve the thermal insulation performance of the aerogel insulation layer. The reinforcing agent can further improve the overall mechanical properties and thermal insulation performance of the composite. After hydrophobic modification, the polyester silica composite can have good hydrophobic properties, further improving the overall moisture resistance of the aerogel insulation film.

[0014] Preferably, the reinforcing material is prepared by the following method:

[0015] The graphene oxide is mixed with deionized water to obtain a graphene oxide dispersion, and ethylenediamine is added and stirred to obtain a reinforced material.

[0016] By adopting the above technical solution, graphene oxide can further improve the compatibility of the system, thereby improving the binding force of the system and at the same time improving the mechanical properties of the aerogel.

[0017] Preferably, the mass concentration of graphene oxide in the graphene oxide dispersion is 3-5 mg / mL.

[0018] By adopting the above technical solution and controlling the mass concentration of graphene oxide in the graphene oxide dispersion within the above range, the stability of the polyester silica aerogel can be further improved.

[0019] Preferably, the hydrophobic modification liquid comprises trimethylchlorosilane, ethanol and n-hexane.

[0020] By adopting the above technical solution, under the action of trimethylchlorosilane, the polyester-silica composite can have good hydrophobic properties, so as to further improve the hydrophobicity and moisture resistance of the overall composite material.

[0021] Preferably, the mass ratio of trimethylchlorosilane, ethanol and n-hexane is: (3.1-3.3):1:6.7.

[0022] Controlling the mass ratio of trimethylchlorosilane, ethanol and n-hexane within the above range can make the polyester-silica composite have better hydrophobic properties.

[0023] In a second aspect, the present application provides a method for preparing an aerogel thermal insulation film, using the following technical solution:

[0024] A method for preparing an aerogel thermal insulation film comprises the following steps:

[0025] S1. Mix Dow Corning 184 silicone and curing agent for 3 minutes, let stand for 30 minutes to remove foam, and evenly apply it on the fluorine release film for later use;

[0026] S2, 9110T and curing agent were uniformly mixed for 3 minutes, allowed to stand for 10 minutes, and foam was removed under vacuum to obtain the mixed 9110T type silica gel; polyester silica composite powder, the mixed 9110T type silica gel, titanium dioxide ultrafine powder, solvent, and flame retardant were uniformly mixed, and then dried to remove excess liquid to obtain a prefabricated mixture;

[0027] S3, spreading the prefabricated mixture obtained in step S2 on the fluorine release film prepared in step S1, and then covering it with a layer of the fluorine release film prepared in step S1, and rolling it to obtain a stretched film;

[0028] S4. Dry the stretched film at a constant temperature of 60°C for 3 hours. After curing, peel off the two layers of fluorine release films at a speed of 1 cm / s in a stable airflow at 60°C, and continue to dry at a constant temperature of 60°C for 1 hour to obtain an aerogel insulation film.

[0029] By adopting the above technical solution, the prefabricated mixture prepared in step S2 is evenly coated on the fluorine release film, so that good peeling properties can be obtained.

[0030] Preferably, the solvent is ethyl acetoacetate or ethyl acetate.

[0031] Preferably, the mass ratio of the polyester silica composite, the mixed 9110T silica gel, the ultrafine titanium dioxide powder, the solvent and the flame retardant is (0.7-0.9):1:0.2:2:0.2.

[0032] Preferably, the aerogel thermal insulation film has a thickness of 0.3-1 mm.

[0033] In summary, the present application includes at least one of the following beneficial technical effects:

[0034] 1. The aerogel thermal insulation film prepared in the present application has good moisture resistance and flame retardant properties, and there is no powder falling. The mechanical strength is greatly improved, and there is no need to attach a protective film or base material with a slightly higher thermal conductivity (such as a PET base film, etc.). In actual use, the thermal insulation effect is better than that of the traditional aerogel thermal insulation film, and the prepared aerogel thermal insulation film is green and environmentally friendly;

[0035] 2. The aerogel thermal insulation film prepared in the present application has good elasticity, can better fill gaps and bridge tolerances when used, and the prepared aerogel thermal insulation film has a lower thickness;

[0036] 3. Treating polyester silica aerogel with graphene oxide can further improve the overall compatibility and mechanical strength of the system, thereby obtaining a more stable aerogel insulation film. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 It is a cross-sectional schematic diagram used to reflect the specific structure of the aerogel thermal insulation film.

[0038] Figure 2 It is a schematic diagram of the surface results of the humidity tolerance test of the sample in Example 3 of the present application.

[0039] Figure 3 It is a schematic diagram of the flame retardant performance test results of the sample of Example 3 in this application.

[0040] Figure 4 It is a schematic diagram of the surface results of the humidity tolerance test of the sample of Comparative Example 4 in the present application.

[0041] Figure 5 It is a schematic diagram of the flame retardant performance test results of the sample of comparative example 4 in the present application.

[0042] 1. The first floor; 2. The second floor; 3. The third floor. DETAILED DESCRIPTION

[0043] The present application is further described in detail below with reference to the embodiments:

[0044] Example 1

[0045] Preparation of graphene composite treatment:

[0046] 1.2 g of graphene oxide was mixed with 400 g of deionized water, and after ultrasonic treatment for 30 min, a graphene oxide dispersion having a graphene oxide concentration of 3 mg / mL was obtained. 2.2 mL of ethylenediamine was added to the graphene oxide dispersion and stirred evenly to obtain a graphene composite treated product.

[0047] Preparation of polyester nanofiber membrane:

[0048] 5 g of polyester was mixed with 45 g of hexafluoroisopropanol, and magnetically stirred for 20 hours to obtain a polyester limiting membrane pre-spinning solution, and the polyester fiber pre-spinning solution was used to prepare a polyester nanofiber membrane by electrospinning.

[0049] Among them, the voltage of electrospinning is 17 kV, the receiving distance is 15 cm, the injection speed is 0.1 mm / min, and the receiving roller speed is 80 r / min.

[0050] Preparation of silanol mixture:

[0051] 8.33 g of tetraethyl orthosilicate, 57.33 g of ethanol and 34.34 g of deionized water were mixed to obtain a mixed solution, and the pH value of the mixed solution was adjusted to 2 using 1 mol / L hydrochloric acid, followed by magnetic stirring for 20 hours to obtain a silanol mixed solution.

[0052] Preparation of polyester nanocomposite nanosilica fiber membrane:

[0053] The polyester nanoconfinement membrane was completely immersed in the above-prepared silanol mixed solution to obtain a mixture, and the pH value of the mixture was adjusted to 6 with 0.5 mol / L ammonia water to obtain a silica wet gel. After aging at 40° C. for 48 h, a polyester composite nano-silica fiber membrane was obtained.

[0054] Preparation of polyester silica composite:

[0055] After mixing 28.7 g of trimethylchlorosilane, 9.26 g of ethanol and 62.04 g of n-hexane, a treatment solution was obtained. The graphene composite treated product prepared above was mixed with the treatment solution, and hexamethyldisilazane and tert-butanol were added. The mixture was kept for 24 hours and dried at 25° C. and normal pressure for 24 hours to obtain a polyester silica composite powder.

[0056] Preparation of aerogel thermal insulation film:

[0057] Take 3g of Dow Corning No. 184 silicone rubber, add 0.3g of curing agent and mix, stir at 1000r / min for 3min, transfer to a vacuum tank, evacuate and let stand for 30min to remove foam to obtain silicone glue, and evenly apply the prepared silicone glue on the fluorine release film. Prepare twice as the first and third layers for standby use.

[0058] Take 3g of 9110T organic silica gel, add 0.3g of curing agent and mix, stir at a speed of 1000r / min for 3min, transfer to a vacuum tank, evacuate and let stand for 10min to remove foam, and obtain the mixed 9110T silica gel for use.

[0059] 2.1g of polyester silica composite powder, 3g of mixed 9110T silica gel, 0.6g of titanium dioxide ultrafine powder, 6g of ethyl acetoacetate, and 0.6g of flame retardant were mixed and coated between the two layers of fluorine release films coated with silicone glue prepared above, so that the two layers of fluorine release films sandwiched the entire system, and then calendered into a thickness of 0.7mm through a mold, and placed in a 60°C forced air drying oven for curing for 3h, and then transferred to a 60°C flowing air place, and the double-layer fluorine release film was peeled off at a speed of 1cm / s. After the product was thoroughly dried, an aerogel thermal insulation film was obtained, and the aerogel thermal insulation film was arranged in the first layer, the second layer, and the third layer in sequence.

[0060] Wherein, the flame retardant is ammonium polyphosphate.

[0061] Example 2

[0062] Preparation of graphene composite treatment:

[0063] 2 g of graphene oxide was mixed with 400 g of deionized water, and after ultrasonic treatment for 30 min, a graphene oxide dispersion having a graphene oxide concentration of 3 mg / mL was obtained. 2.2 mL of ethylenediamine was added to the graphene oxide dispersion and stirred evenly to obtain a graphene composite treated product.

[0064] Preparation of polyester nanofiber membrane:

[0065] 7 g of polyester was mixed with 63 g of hexafluoroisopropanol, and magnetically stirred for 20 hours to obtain a polyester limiting membrane pre-spinning solution, and the polyester fiber pre-spinning solution was used to prepare a polyester nanofiber membrane through electrostatic spinning.

[0066] Among them, the voltage of electrospinning is 17 kV, the receiving distance is 15 cm, the injection speed is 0.1 mm / min, and the receiving roller speed is 80 r / min.

[0067] Preparation of silanol mixture:

[0068] 7.69 g of tetraethyl orthosilicate, 53.85 g of ethanol and 38.46 g of deionized water were mixed to obtain a mixed solution, and the pH value of the mixed solution was adjusted to 2 using 1 mol / L hydrochloric acid, followed by magnetic stirring for 20 hours to obtain a silanol mixed solution.

[0069] Preparation of polyester nanocomposite nanosilica fiber membrane:

[0070] The polyester nanoconfinement membrane was completely immersed in the above-prepared silanol mixed solution to obtain a mixture, and the pH value of the mixture was adjusted to 6 with 0.5 mol / L ammonia water to obtain a silica wet gel. After aging at 40° C. for 48 h, a polyester composite nano-silica fiber membrane was obtained.

[0071] Preparation of polyester silica composite:

[0072] 30 g of trimethylchlorosilane, 9.09 g of ethanol and 60.91 g of n-hexane were mixed to obtain a treatment solution, the graphene composite treated product prepared above was mixed with the treatment solution, and hexamethyldisilazane and tert-butanol were added, kept for 24 hours, and dried at 25° C. and normal pressure for 24 hours to obtain a polyester silica composite powder.

[0073] Preparation of aerogel thermal insulation film:

[0074] Take 3g of Dow Corning No. 184 silicone rubber, add 0.3g of curing agent and mix, stir at 1000r / min for 3min, transfer to a vacuum tank, evacuate and let stand for 30min to remove foam to obtain silicone glue, and evenly apply the prepared silicone glue on the fluorine release film. Prepare twice as the first and third layers for standby use.

[0075] Take 3g of 9110T organic silica gel, add 0.3g of curing agent and mix, stir at a speed of 1000r / min for 3min, transfer to a vacuum tank, evacuate and let stand for 10min to remove foam, and obtain the mixed 9110T silica gel for use.

[0076] 2.7g of polyester silica composite powder, 3g of mixed 9110T silica gel, 0.6g of titanium dioxide ultrafine powder, 6g of ethyl acetoacetate, and 0.6g of flame retardant were mixed and coated between the two layers of fluorine release film coated with silicone glue prepared above, so that the two layers of fluorine release film sandwiched the entire system, and then calendered into a thickness of 0.7mm through a mold, and placed in a 60°C forced air drying oven for curing for 3h, and then transferred to a 60°C flowing air place, and the double-layer fluorine release film was peeled off at a speed of 1cm / s. After the product was thoroughly dried, an aerogel thermal insulation film was obtained, and the aerogel thermal insulation film was arranged in the first layer, the second layer, and the third layer in sequence.

[0077] Wherein, the flame retardant is ammonium polyphosphate.

[0078] Example 3

[0079] Preparation of graphene composite treatment:

[0080] 1.6 g of graphene oxide was mixed with 400 g of deionized water, and after ultrasonic treatment for 30 min, a graphene oxide dispersion having a graphene oxide concentration of 3 mg / mL was obtained. 2.2 mL of ethylenediamine was added to the graphene oxide dispersion and stirred evenly to obtain a graphene composite treated product.

[0081] Preparation of polyester nanofiber membrane:

[0082] 6 g of polyester was mixed with 54 g of hexafluoroisopropanol, and magnetically stirred for 20 hours to obtain a polyester limiting membrane pre-spinning solution, and the polyester fiber pre-spinning solution was used to prepare a polyester nanofiber membrane by electrospinning.

[0083] Among them, the voltage of electrospinning is 17 kV, the receiving distance is 15 cm, the injection speed is 0.1 mm / min, and the receiving roller speed is 80 r / min.

[0084] Preparation of silanol mixture:

[0085] 8 g of tetraethyl orthosilicate, 56 g of ethanol and 36 g of deionized water were mixed to obtain a mixed solution, and the pH value of the mixed solution was adjusted to 3 using 1 mol / L hydrochloric acid, followed by magnetic stirring for 20 hours to obtain a silanol mixed solution.

[0086] Preparation of polyester nanocomposite nanosilica fiber membrane:

[0087] The polyester nanoconfinement membrane was completely immersed in the above-prepared silanol mixed solution to obtain a mixture, and the pH value of the mixture was adjusted to 6 with 0.5 mol / L ammonia water to obtain a silica wet gel. After aging at 40° C. for 48 h, a polyester composite nano-silica fiber membrane was obtained.

[0088] Preparation of polyester silica composite:

[0089] After mixing 29.36 g of trimethylchlorosilane, 9.17 g of ethanol and 61.47 g of n-hexane, a treatment solution was obtained. The graphene composite treated product prepared above was mixed with the treatment solution, and hexamethyldisilazane and tert-butanol were added. The mixture was kept for 24 hours, and dried at 25° C. and normal pressure for 24 hours to obtain a polyester silica composite powder.

[0090] Preparation of aerogel thermal insulation film:

[0091] Take 3g of Dow Corning No. 184 silicone rubber, add 0.3g of curing agent and mix, stir at 1000r / min for 3min, transfer to a vacuum tank, evacuate and let stand for 30min to remove foam to obtain silicone glue, and evenly apply the prepared silicone glue on the fluorine release film. Prepare twice as the first and third layers for standby use.

[0092] Take 3g of 9110T organic silica gel, add 0.3g of curing agent and mix, stir at a speed of 1000r / min for 3min, transfer to a vacuum tank, evacuate and let stand for 10min to remove foam, and obtain the mixed 9110T silica gel for use.

[0093] 2.4g of polyester silica composite powder, 3g of mixed 9110T silica gel, 0.6g of titanium dioxide ultrafine powder, 6g of ethyl acetoacetate, and 0.6g of flame retardant were mixed and coated between the two layers of fluorine release films coated with silicone glue prepared above, so that the two layers of fluorine release films sandwiched the entire system, and then calendered into a thickness of 0.7mm through a mold, placed in a 60°C forced air drying oven for curing for 3h, and then transferred to a 60°C flowing air place, and the double-layer fluorine release film was peeled off at a speed of 1cm / s. After the product was thoroughly dried, an aerogel thermal insulation film was obtained, and the aerogel thermal insulation film was arranged in the first layer, the second layer, and the third layer in sequence.

[0094] Wherein, the flame retardant is ammonium polyphosphate.

[0095] Example 4

[0096] Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that in Example 4, 0.8 g of graphene oxide is added when preparing the graphene oxide dispersion.

[0097] Example 5

[0098] Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that in Example 5, 2.4 g of graphene oxide is added when preparing the graphene oxide dispersion.

[0099] Example 6

[0100] Example 6 is based on Example 3. The difference between Example 6 and Example 3 is that in Example 6, when preparing the hydrophobic modification liquid, 26.67 g of trimethylsilyl chloride, 9.52 g of ethanol and 63.81 g of n-hexane are added.

[0101] Example 7

[0102] Example 7 is based on Example 3. The difference between Example 7 and Example 3 is that in Example 7, when preparing the hydrophobic modification liquid, 31.25 g of trimethylsilyl chloride, 8.93 g of ethanol and 59.82 g of n-hexane are added.

[0103] Comparative Example 1

[0104] Comparative Example 1 is based on Example 3. The difference between Comparative Example 3 and Example 3 is that when preparing the aerogel insulation film in Comparative Example 1, 1.61g of 9110T silica gel, 1.79g of polyester silica composite powder and 3.6g of ethyl acetoacetate are mixed and then coated between two layers of fluorochemical release films coated with silicone glue.

[0105] Comparative Example 2

[0106] Comparative Example 2 is based on Example 3. The difference between Comparative Example 2 and Example 3 is that in Comparative Example 2, when preparing the aerogel insulation film, 1.32g of 9110T silica gel, 1.89g of polyester silica composite powder and 3.79g of ethyl acetoacetate are mixed and then coated between two layers of fluorine release film coated with silicone glue.

[0107] Comparative Example 3

[0108] Comparative Example 3 is based on Example 3. The difference between Comparative Example 3 and Example 3 is that in Comparative Example 3, when preparing the aerogel insulation film, 1.47 g of 9110T silica gel, 1.84 g of polyester silica composite powder and 3.69 g of ethyl acetoacetate are mixed and then coated between two layers of fluorochemical release films coated with silicone glue.

[0109] Comparative Example 4

[0110] Comparative Example 4 uses a commercially available common PTE-based thermal insulation film.

[0111] Reference Figure 1 The aerogel thermal insulation film after thorough drying includes a first layer 1, a second layer 2 and a third layer 3, the first layer 1 and the third layer 3 are both siloxane cured protective layers, the second layer 2 is an aerogel thermal insulation layer, and the second layer 2 is located between the first layer 1 and the third layer 3.

[0112] Performance testing

[0113] The aerogel thermal insulation films prepared in Examples 1-7 and Comparative Examples 1-4 were subjected to the following performance tests:

[0114] (1) Thermal conductivity test

[0115] The thermal conductivity of the prepared aerogel insulation film was tested by a Hot Disk thermal constant analyzer. Each sample was tested three times, the average value was taken, and the test results were filled in Table 1.

[0116] (2) Humidity tolerance test

[0117] The above samples were kept at 25°C and 85% humidity for 168 hours, and the adhesion was tested using tape. Each sample was tested three times, and the test results were filled in Table 1.

[0118] (3) Flame retardant performance test

[0119] Burn the sample, observe the burning phenomenon of the sample, and fill in the test results in Table 1.

[0120] Table 1 Performance test results of Examples 1-9 and Comparative Examples 1-4

[0121]

[0122]

[0123] Data analysis

[0124] The thermal conductivity of Examples 1-3 is all 0.037 W·m -1 ·K -1 And the following illustrate that the aerogel thermal insulation film prepared by the present application has good thermal insulation performance; after Example 1-3 used tape to test the adhesion performance of the product surface in a humid environment for 168 hours, the surface of the sample was smooth, without warping or blistering, indicating that the aerogel thermal insulation film prepared by the present application has good resistance to humid environments; after burning, Examples 1-3 produced non-combustible gray-white powder and no odor, indicating that the aerogel thermal insulation film prepared by the present application has good high temperature resistance and flame retardant properties.

[0125] When the content of graphene oxide in the graphene oxide dispersion is too much, the graphene oxide will agglomerate in the system, thereby reducing the overall stability of the system; when the content of graphene oxide is too little, the improvement of the mechanical properties, thermal insulation properties, and hydrophobicity of the polyester silica composite is reduced; therefore, the thermal insulation properties and moisture resistance of Examples 4 and 5 are reduced.

[0126] When the content of trimethylchlorosilane is too much, it will also affect the stability of the system; when the content of trimethylchlorosilane is too little, it will make it difficult for graphene oxide to compound with the polyester composite nano-silica fiber membrane and adhere to the surface of silica, so the performance improvement effect of the polyester composite nano-silica fiber membrane is reduced, so the performance of Example 6 and Example 7 is reduced.

[0127] In Comparative Examples 1, 2 and 3, no ultrafine titanium dioxide powder and flame retardant are added, so the infrared reflection shielding effect is reduced, and the thermal insulation performance is reduced. At the same time, without the flame retardant, the system will also cause slow combustion.

[0128] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. An aerogel thermal insulation film, characterized in that: It comprises a first layer, a second layer and a third layer, wherein the first layer and the third layer are both siloxane cured protective layers, and the second layer comprises an aerogel heat insulation layer; The siloxane cured protective layer is Dow Corning No. 184 silicone; The aerogel heat insulation layer comprises a silica gel matrix, ultrafine titanium dioxide powder, a flame retardant, and a polyester silica composite; the silica gel matrix comprises 9110T silica gel; The polyester-silica composite is prepared by the following method: The polyester is mixed with hexafluoroisopropanol, and the mixture is stirred and then spun to obtain polyester fibers; after tetraethyl orthosilicate, ethanol and deionized water are mixed, the pH value is adjusted to 2-3, a reinforcing material is added, and the mixture is stirred to obtain a silanol mixed solution; the polyester fiber is immersed in the silanol mixed solution, the pH value is adjusted to weak acidity, and a polyester silica preform is obtained; the polyester silica preform is immersed in a hydrophobic modification solution for hydrophobic modification, and then transferred to a n-hexane solution, and dried to obtain a polyester silica composite; The method for preparing the aerogel thermal insulation film comprises the following steps: S1. Mix Dow Corning 184 silicone and curing agent for 3 minutes, let stand for 30 minutes to remove foam, and evenly apply it on the fluorine release film for later use; S2, 9110T and curing agent were uniformly mixed for 3 minutes, allowed to stand for 10 minutes, and foam was removed under vacuum to obtain the mixed 9110T type silica gel; polyester silica composite powder, the mixed 9110T type silica gel, titanium dioxide ultrafine powder, solvent, and flame retardant were uniformly mixed, and then dried to remove excess liquid to obtain a prefabricated mixture; S3, spreading the prefabricated mixture obtained in step S2 on the fluorine release film prepared in step S1, and then covering it with a layer of the fluorine release film prepared in step S1, and rolling it to obtain a stretched film; S4, drying the stretched film at a constant temperature of 60°C for 3 hours, peeling off the two layers of fluorine release films at a speed of 1 cm / s in a stable airflow at 60°C after curing, and continuing to dry at a constant temperature of 60°C for 1 hour to obtain an aerogel thermal insulation film; The mass ratio of the polyester silica composite powder, the mixed 9110T silica gel, the ultrafine titanium dioxide powder, the solvent and the flame retardant is (0.7-0.9):1:0.2:2:0.2; The hydrophobic modification liquid includes trimethylchlorosilane, ethanol and n-hexane; The mass ratio of trimethylchlorosilane, ethanol and n-hexane is (3.1-3.3):1:6.

7.

2. The aerogel thermal insulation film according to claim 1, characterized in that: The reinforcing material is prepared by the following method: The graphene oxide is mixed with deionized water to obtain a graphene oxide dispersion, and ethylenediamine is added and stirred to obtain a reinforced material.

3. The aerogel thermal insulation film according to claim 2, characterized in that: The mass concentration of graphene oxide in the graphene oxide dispersion is 3-5 mg / mL.

4. The aerogel thermal insulation film according to claim 1, characterized in that: The solvent is ethyl acetoacetate or ethyl acetate.

5. The aerogel thermal insulation film according to claim 1, characterized in that: The thickness of the aerogel thermal insulation film is 0.3-1 mm.

Citation Information

Patent Citations

  • Novel aerogel heat insulation film

    CN111777958A

  • Polyester nanofiber / silicon dioxide composite aerogel film and preparation method thereof

    CN114436624A